The use of evidence provided by healthcare professionals as expert witness in sexual violence trials in Gauteng province, South Africa - Mooa, Ramadimetja Shirley (University of Pretoria, 2024)
Dissertation (MNur (Nursing Science))--University of Pretoria, 2024.